Implementasi Algoritma AES (Advanced Encryption Standard) Untuk Keamanan File Hasil Radiologi di RSU Imelda Medan - Hulu, Delisman; Nadeak, Berto; Aripin, Soeb (STMIK Budi Darma, 2020)
Data security is very important for all users of an information system, recently cryptography has become the method used in data. Cryptography is the study of mathematical techniques in an original information or message (plaintext) into a hidden text (Chipertext) and then converted into the original message again. Cryptography has three important elements, namely key generation, encryption and description. In cryptography, the block cipher algorithm is known, which includes AES (Advanced Encyption Standard) which is part of the Modern Symmetric Key Cipher, this algorithm uses the same key during the encryption and description processes so that the data we have will be difficult to cooperate with its meaning. The algorithmic technique is used to measure data in the form of certain codes, for the purpose of so that the stored information cannot be read by anyone except authorized people. Therefore, a data security system is needed in sending radiological results to patients because radiological results are confidential to patients.Keywords: Algorithm, AES, Encryption, Description, Cryptography